Instructional Model Development through the Application of Sufficient Economy Philosophy Emphasizing Thinking Process and Vidisa Samadhi to Enhance the Ability of Research for Learning Development in English for Teacher Students - Termsinsuk, Saisunee; Intachai, Sunisa (Ratchaphruek Journal, 2020)
The purposes of this research were:1) to develop an instructional model through the application of sufficient economy philosophy emphasizing thinking process and Vidisa Samathi (Meditation) to enhance the research ability in English learning development for student teachers; and 2) to investigate the research ability of student teachers for learning development in English via the instructional developed model. The study was conducted in 3 phases: 1) Analyzing context and constructing a conceptual framework; 2) Synthesizing the instructional model; and 3) Investigating the research ability in English learning development of the students through the implementation of the instructional model. A target group of 17 student teachers majoring in English at the Nakhon Ratchasima Rajabhat University was investigated in the academic year 2018. The research instruments employed in the study were semi-structured interviews, observation forms, and evaluation forms. Data were analyzed by using typology technique, percentage, and means. The study developed an instructional model with seven components, and five instructional steps: Preparing; Thinking process for planning; Thinking for acting; Thinking for reflecting; and Thinking for examining. The results after using the model revealed that the student teachers’ competency meets the designated criteria. The effective model was named, SEP-V model.